Big tech, knowledge predation and the implications for development - Rikap, Cecilia; Lundvall, Bengt-Åke (Innovation and development, 2022)
This paper focuses on tech giants as active drivers of a phase of globalization characterized by growth in digital services trade combined with a general shift to intangible assets. By analysing how Google, Amazon and Microsoft organize their innovation activities, we show that they continuously monopolize knowledge while outsourcing innovation steps to other firms and research institutions. The paper compares science and technology collaborations with patent co-ownership suggesting knowledge predation from those other organizations. We also highlight that selected tech giants combine the collection of innovation rents with rents from exclusive access to data. We, therefore, refer to tech giants as data-driven intellectual monopolies, each organizing and controlling a global corporate innovation system (CIS). Intellectual monopolies predate knowledge (including data when they are data-driven) from their CIS that they turn into intangible assets. The paper ends with reflections on the implications for innovation and development.